Plant-Based Anti-Inflammatory Agents: A Scientific Review of Bioactive Compounds and Mechanisms - Samiappan, Kavitha; Chalakoth, Jyothsna (Asian Journal of Biological and Life Sciences, 2025)
Inflammation, caused by pathogens or damaged tissues, can lead to chronic diseases if left untreated. Although they provide relief, contemporary anti-inflammatory treatments-in particular, non-steroidal anti-inflammatory medicines, or NSAIDs-frequently have side effects. Because of their capacity to modify important inflammatory pathways like Cyclooxygenase (COX), Nitric Oxide Synthase (NOS), and Nuclear Factor kappa B (NF-κB), plant-derived chemicals have recently come to light as possible substitutes. Curcumin, resveratrol, and Capsaicin are examples of phytochemicals that have demonstrated strong anti-inflammatory properties by preventing oxidative stress and pro-inflammatory cytokines. Furthermore, green tea polyphenols and omega-3 fatty acids show great therapeutic promise in lowering inflammation and preventing chronic illnesses like cardiovascular disease and arthritis. Even though these plant-based treatments have potential, further research is needed to fully comprehend their molecular mechanisms and create clinically useful formulations. Inflammatory disorders may have safer, more sustainable therapy alternatives if medicinal plants are incorporated into traditional healthcare.
Keywords: Anti-inflammatory; Cyclooxygenase (COX); Nitric Oxide Synthase (NOS); Omega-3 fatty acids